Speak & listening skills - Marks, Jon. (Peaslake : Delta Publishing, 2013)
Suitable for achieving 6.5 or higher in the Speaking and Listening modules of the IELTS exam, this title shows students how to give the well-structured, detailed replies that examiners are looking for in the speaking module.
Introduction About the Speaking test About the Listening test The IELTS Scoring system Unit 1 Personal circumstances Unit 2 Leisure interests Unit 3 Finding your own path Unit 4 Equal opportunities? Unit 5 Getting from A to B Unit 6 Dumbed down? Unit 7 The world's your oyster Four practice Speaking tests Unit 8 Getting things sorted out Unit 9 Looking at the bigger picture Audio transcripts Answer key
language bookfair2015
Keywords: International English Language Testing System; English language -- Examinations, questions, etc; English language -- Problems, exercises, etc; English language -- Examinations -- Study guides